State-business relations and access to external financing - Andrey Tkachenko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
Firms' contractual relations with a state may give lenders a positive signal and facilitate access to debt. This paper studies the impact of public procurement contracts on ftrms' access to debt using an extensive survey of Russian manufacturing ftrms combined with accounting and procurement data. It shows that earnings from state-to-business contracts increase the short-term debt twice as much as revenue from private contracts. Long-term debt is not affected by public contracts differently compared to private contracts. The debt sensitivity to public contracts is four times larger for politically connected ftrms, although it is still positive and signiftcant for non-connected and small ftrms. The paper concludes that political connection does not entirely suppress the beneftcial access to debt that public contracts create.
urn:nbn:fi:bof-202210251419
Keywords: G18; G32; H57; 330; public procurement; political connection; leverage; short-term debt; long-term debt; capital structure; Russia